PENGARUH METODE ROLE PLAYING TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN ISI DONGENG DI SMP YAPIDA CISAYONG TASIKMALAYA - Fuadah, Elly Samrotul; Triwahyuni, Heti (JALADRI : Jurnal Ilmiah Program Studi Bahasa Sunda, 2017)
the result of research on the influence of methods Role Playing on the ability to understand the content fairytale Seventh Grade Students of SMP YAPIDA Cisayong Tasikmalaya. Abilty understand the contents of a fairy tale in the junior class VII YAPIDA Cisayong Tasikmalaya before using Method Role Playing result quite satisfactory, because it is different. The Role Playing method is used to improve the ability to understand the fairy tales of students applied in pretest and postes as "acts". And the existing data and whether the data and data that there is data. Test gain (difference data hasilanalisis) and hypothesis test (measurement epektip not the result of analysis). Of the 34 students 27 (79.4%) students have been able to play, while 7 (20.6%) of students still do not understand the contents of a fairy tale mampuh. The ability of students in postesbisa in total score averaged 20.1 There is a significant difference between the ability of students before and after using the method of role playing, it can be seen from testing the hypothesis. Therefore, we can conclude this study to understand the lesson effective in letting improve fairytale Class VII student of SMP YAPIDA Cisayong Tasikmalaya. Role Playing method has been proven effective in improving the ability to understand the contents of fairy tales can also utilized for other lessons.